2015
DOI: 10.1074/jbc.m114.634311
|View full text |Cite
|
Sign up to set email alerts
|

Procollagen Lysyl Hydroxylase 2 Expression Is Regulated by an Alternative Downstream Transforming Growth Factor β-1 Activation Mechanism

Abstract: Background: PLOD2 expression and subsequent collagen pyridinoline cross-links are induced in fibrotic tissues by TGF␤1. Results: TGF␤1 induces changes to histone modifications. SP1 and SMAD3 but not P300/CBP are responsible for PLOD2 induction. Conclusion: SMAD3 regulates TGF␤1-induced PLOD2 expression via histone-modifying enzymes other than the currently known downstream effectors. Significance: Unraveling PLOD2 transcriptional regulation would provide new ways to interfere in fibrotic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 65 publications
5
51
0
3
Order By: Relevance
“…It has been reported that LH2 is regulated at the transcriptional level by hypoxia-inducible factor 1α, TGF-β and several profibrotic cytokines, c-Myb, and microRNA-26a/b12133435363738. Our finding that LH2 protein levels were similar between Fkbp10 +/+ and Fkbp10 −/− MEFs indicates that LH2 function is regulated post-translationally by FKBP65.…”
Section: Discussionsupporting
confidence: 68%
“…It has been reported that LH2 is regulated at the transcriptional level by hypoxia-inducible factor 1α, TGF-β and several profibrotic cytokines, c-Myb, and microRNA-26a/b12133435363738. Our finding that LH2 protein levels were similar between Fkbp10 +/+ and Fkbp10 −/− MEFs indicates that LH2 function is regulated post-translationally by FKBP65.…”
Section: Discussionsupporting
confidence: 68%
“…After 24 h, total RNA was extracted using TRIzol reagent (Invitrogen), and 1 μ g of RNA was converted into cDNA using the ImProm‐II Reverse Transcription System (Promega, Madison, WI, USA). Quantitative real‐time PCR procedures were performed using LightCycler 480 SYBR Green I Master (Roche Diagnostics, Mannheim, Germany), an equal amount of cDNA, and specific primers for genes encoding type I collagen and its modifying enzymes, as follows: collagen type I alpha‐2 chain ( COL1A2 ) , 5′‐TAATGGGGAAGCTGGATCTG‐3′ (forward) and 5′‐GTCCCTGAGCACCATTGTTT‐3′ (reverse); LH1 ( PLOD1 ) , 5′‐GAAGCTCTACCCCGGCTACT‐3′ (forward) and 5′‐CTTGTAGCGGACGACAAAGG‐3′ (reverse); LH2 ( PLOD2 ) , 5′‐GGGAGTTCATTGCACCAGTT‐3′ (forward) and 5′‐GAGGACGAAGAGAACGCTGT‐3′ (reverse); LH3: PLOD3 , 5′‐CACTACGGCCAGTGGTCAG‐3′ (forward) and 5′‐GTGGGCACATTCTCGTAGC‐3′ (reverse); GLT25D1 ( GLT25D1 ) , 5′‐GATGCTGCCTGTGGACGAGTTC‐3′ (forward) and 5′‐CTCACATAGCCATCGTCTCCTG‐3′ (reverse); LOX ( LOX ) , 5′‐CGCTGTGACATTCGCTACACAGGAC‐3′ (forward) and 5′‐CATTGGGAGTTTTGCTTTGCCTTCT‐3′ (reverse); and glyceraldehyde‐3‐phosphate dehydrogenase ( GAPDH ) , 5′‐GCTCTCCAGAACATCATCC‐3′ (forward) and 5′‐GTGTCGCTGTTGAAGTCAG‐3′ (reverse). Results were analyzed using the LightCycler 480 Instrument (Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…TGFβ1 strongly induces collagen type I and LH2 expression in fibroblasts (45)(46)(47). We performed immunocytochemistry to verify the expression of LH2, FKBP65, and procollagen type Iα1 after TGFβ1 stimulation of primary dermal fibroblasts.…”
Section: Lh2 Splicementioning
confidence: 99%